Causes of death in childhood‐onset Type 1 diabetes: long‐term follow‐up. Issue 1 (7th April 2016) - Gagnum, V.; Stene, L. C.; Jenssen, T. G.; Berteussen, L. M.; Sandvik, L.; Joner, G.; Njølstad, P. R.; Skrivarhaug, T.
Abstract: Aims: To assess the causes of death and cause‐specific standardized mortality ratios in two nationwide, population‐based cohorts diagnosed with Type 1 diabetes during the periods 1973–1982 and 1989–2012, and to evaluate changes in causes of death during the follow‐up period. Methods: People with Type 1 diabetes who were aged < 15 years at diagnosis were identified in the Norwegian Childhood Diabetes Registry and followed from diagnosis until death, emigration or September 2013 ( n = 7871). We assessed causes of death by linking data to the nationwide Cause of Death Registry and through a review committee that evaluated medical records, autopsy reports and death certificates. Results: During a mean (range) follow‐up of 16.8 (0–40.7) years, 241 individuals (3.1%) died, representing 132 143 person‐years. The leading cause of death before the age of 30 years was acute complications (41/119, 34.5%). After the age of 30 years cardiovascular disease was predominant (41/122, 33.6%), although death attributable to acute complications was still important in this age group (22/122, 18.0%). A total of 5% of deaths were caused by 'dead‐in‐bed' syndrome. The standardized mortality ratio was elevated for cardiovascular disease [11.9 (95% CI 8.6–16.4)] and violent death [1.7 (95% CI 1.3–2.1)] in both sexes combined, but was elevated for suicide only in women [2.5 (95% CI 1.2–5.3)]. The risk of death from acute complications was approximately half in women compared with men [hazard ratio 0.43 (95% CI 0.25–0.76)], and did not change with more recent year of diagnosis [hazard ratio 1.02 (0.98–1.05)]. Conclusions: There was no change in mortality attributable to acute complications during the study period. To reduce premature mortality in people with childhood‐onset diabetes focus should be on prevention of acute complications. Male gender implied increased risk. What's new?: This nationwide, population‐based study is a long‐term follow‐up of two cohorts, diagnosed with childhood‐onset Type 1 diabetes in 1973–1982 and 1989–2012 [mean (range) follow‐up 16.8 (0–40.7) years]. The study addresses cause‐specific mortality based on clinical information in addition to high‐quality register data. The leading cause of death before the age of 30 years was acute complications; after the age of 30 years cardiovascular death was predominant. In spite of improved diabetes care during the study period we report no change in mortality attributable to acute complications. Our results indicate a need to improve diabetes management and psychosocial care to prevent premature mortality.